Graph usage in financial reports: evidence from Portuguese listed companies - Bastardo, Ana Clara Lopes Beato Balça (2015)
When assessing investment options, investors focus on the graphs of annual reports, despite lack of auditing. If poorly constructed, graphs distort perceptions and lead to inaccurate decisions. This study examines graph usage in all the companies listed on Euronext Lisbon in 2013. The findings suggest that graphs are common in the annual reports of Portuguese companies and that, while there is no evidence of Selectivity Distortion, both Measurement and Orientation Distortions are pervasive. The study recommends the auditing of financial graphs, and urges preparers and users of annual reports to be wary of the possibility of graph distortion.